Anatomia e ecofisiologia da interação entre a hemiparasita Psittacanthus robustus e Qualea cordata - Mateus Scarpelli Aguiar Marcato de Paula (2015)
The physiological, anatomical and phenological aspects of the interaction between Psittacanthus robustus (Loranthaceae), a hemiparasite of aerial parts, and Qualea cordata (Vochysiaceae) were accessed in a cerrado area in the National Park of Serra do Cipó, Minas Gerais, Brazil. The physiological parameters analyzed were related to the hydric relations and photossinthetic balance. The leaf and stem anatomy and the interface between the hemiparasite and the host plant were analyzed. The vegetative and reproductive phenology was also presented. The parasitism had significantly effected the physiology of the host plant during the rainy season, interfering in the hydric potential and in the Fv/Fm, although there was no difference in the concentration of photossinthetic pigments. No influence was observed in the dry season. There was no significant difference in the leaf anatomy between the parasited and the non-parasited plants of Q. cordata. The parasitism affected the reproductive phenology of the parasited plants, but there was no statistical difference in the vegetative phenology. The senescence period was longer and a delay in the emission of new leaves was observed in parasited plants. The hemiparasite had unusual hydric relations, demonstrated by greater values of hydric and osmotic potential and lower values of stomatal conductance, which differed from data in the literature for parasitic plants. These features can be explained by the ability of storing water in its succulent leaves, without suffering with low water availability of the cerrado, even during the dry season. The Fv/Fm values demonstrated a tipical behavior of plants adapted to lower irradiance levels, suffering photoinibition during the dry season. Current data evidenced novelties about the parasitism between these two species, which revealed unusual strategies by the hemiparasite for water acquisition, and reinforced the need of expanding our knowledge about parasitic plants of cerrado.